LANGUAGE AND CULTURE MEDIATION AMONG LEGAL SYSTEMS THROUGH SPECIALIZED CONCEPTS INTERPRETATION: FRAME-BASED APPROACH - Atabekova, Anastasia A.; Gorbatenko, Rimma G.; Shoustikova, Tayana V. (International Journal of Psychosocial Rehabilitation, 2020)
The paper explores the hypothesis that argues for the necessity to incorporate frame-based approach into language and culture mediation between two/among several legal systems. The article aims to consider the implementation of frame-based approach to the legal concepts interpretation in the course mediation between two legal systems. To this end, the research includes a number of steps. Among them there is the identification of specialized concept essence within the language and culture mediation framework; analysis of challenges regarding language tools and legal knowledge integration to render the legal concepts meaning in the course of mediation between two legal systems; observation of stages of frame-based approach to interpretation of legal concepts in the course of mediation between two legal systems. The research methodology integrates theoretical and empirical studies that stand on qualitative research paradigm. The study uses comparative ethnographic approach, case study and grounded theory techniques. The analysis operates with the translation techniques terminology. The research stood within English-Russian legal knowledge settings. The on-line English- Russian law dictionary was used to select the concepts as the dictionary is based of UNO multilingual texts corpus (Dictionary reverse.net- on-line). The techniques to analyze parallel corpus mining by the use of bilingual definitions correlations were applied to content analysis of the source and target legal concepts definitions. Cluster analysis was used to structure the empirical data. The research findings confirm the relevance of the approach under study.